Language Personality in the Russian Linguistic Tradition: Diachronic-Synchronic Aspects - Yudina, Natalia (Respectus Philologicus, 2012)
The article is devoted to the analysis of one of the most important terms in modern linguistic usage – the definition of a language personality. It was introduced in Russian-language scientific use in the 1930s by academician V. Vinogradov, and has been related to the ever-increasing interest in the anthropocentric factor in language, as well as to changes in the scientific linguistic paradigm, since the 1980s. Resuming some terminological and conceptual descriptions of language personality, as represented in the Russian-language linguistic literature, this article comes to the conclusion that language personality theory is presently reviewed in linguodidactics, linguoculturology, cognitive linguistics, ethnolinguoculturology, psycholinguistics, lexicography, stylistics, pragmatics, and other intra- and extralinguistic disciplines.The complex analysis makes it possible to identify verbal-semantic (lexicon), linguocognitive (thesaurus), motivational (pragmaticon; cf.Y. N. Karaulov), stylistic, communicative-pragmatic, linguoculturological, emotional, articulatory, and other levels. In addition to language personality, the terms verbal and communicative personality must also be specified and systematized. Further conceptual and terminological research in the description of language personality seems highly necessary for modern linguistics. The process of developing and establishing a language personality appears to be an essential component of the objective and subjective transformations of the information society. Further inquiry into the study of language personality will contribute to a better understanding of the social-political, economic, socio-cultural and linguistic processes occurring in the 21st century.
Keywords: anthropocentric factor; language personality; language personality conception; levels of a language personality; verbal personality; communicative personality; linguodidactic model; the Russian language; extralinguistic disciplines